Relationship Between Physical Activity and Junk Food Consumption on the Incidence of Early Menarche - Beatrix Elizabeth; Ika Juita Giyaningtyas; Aprilina Sartika (PROMOTOR, 2024)
Puberty is a period of change between childhood and adolescence towards adulthood. Early puberty or also called precocious puberty is when girls have signs of puberty before the age of 11 years. The incidence of early menarche in adolescents is increasing in Indonesia. Early menarche increases the risk of cancer such as breast cancer, abdominal obesity, fat accumulation in adipose tissue, cardovascular disease, hypertension and premarital pregnancy. In adolescence, lifestyles and habits change, and one of them is trying new foods. This study identifies whether there is an association between fast food factors and adolescent activity with the occurrence of early menarche. The results of the study on 40 elementary school students in Cikarang female students who did not have early menarche were 20 (50.0%) and female students who had early menarche were 20 (50.0%). In an unhealthy lifestyle and early menarche as many as 14 or 70.0% of students. As for the physical activity of sports schoolgirls with the category of light exercise and early menarche as many as 7 or 35.0%. in students often consume Fast Food and early menarche as many as 15 or 75.0%.